Religion and State in the Islamic Political Paradigm in Indonesia Perspective of Prof. Kamsi - Karimullah, Suud Sarim (Analisis: Jurnal Studi Keislaman, 2022)
The relationship between religion and the state has always been an actual problem in the discourse of Islamic political thought. This paper aims to describe the relationship between religion and the state in Indonesia with a focus on studying the Islamic political paradigm in the view of Prof. Kamsi, who is one of the professors in the study of Islamic law politics at UIN Sunan Kalijaga Yogyakarta. Then, library research with analytical descriptive nature is used in this research by conducting a descriptive study that aims to provide answers to various problems regarding the state of a particular subject or object in detail. Then, various data that have been obtained are analyzed and interpreted to get an adequate explanatory meaning. Furthermore, this study states that in the view of Prof. Kamsi. In general, the pattern of relations between religion and the state is not just a pattern of dichotomous relations that cancel each other out. However, the relationship between religion and the state must be harmoniously and proportionally established. This is intended so that the thinking process of Muslims will not be disturbed by the development of a country that is pioneering and building a better and functioning state order for the long term.